EVALUATION OF THE EFFECTIVENESS OF BUREAUCRATIC SYSTEMS IN PROVIDING PUBLIC SERVICES: USER AND BENEFICIARY PERSPECTIVE - Melyana R Pugu; Yeti Rohayati; Karman (ADMIN: Jurnal Administrasi Negara, 2024)
The study examines the effectiveness of bureaucratic systems in the provision of public services from two main perspectives: service users and beneficiaries. The study aims to evaluate the extent to which the bureaucracy system meets the needs and expectations of the two related groups, analyzes the factors that contribute to the efficiency and efficiency of public service, and identifies strategies to improve the quality of service. The method used in this research is literature. The results show that the satisfaction of users and beneficiaries of public services is influenced by several key factors, including accessibility of services, efficiency of bureaucratic processes, transparency and accountability, as well as the quality of interaction between service providers and the public. Although improvements have been made in some aspects of the service, the study identifies critical areas that need reform and innovation, such as improved technology integration into the service process, training and development of competence of bureaucracy apparatus, and improved public participation mechanisms in policymaking.